Preresection Stained Glue Injection to Localize Pulmonary Small Nodules and Ground-glass Opacities. Issue 4 (July 2020) - Wang, Jian; Gao, Li-Bin; Zhang, Hong; Wang, Jian; Liu, Liang; Shi, Wan-Yin
Abstract : Objective: We sought to introduce a localization procedure (methylene blue-stained N-butyl cyanoacrylate and N-octyl cyanoacrylate glue) in localizing pulmonary small nodules and ground-glass opacities before thoracoscopic resection, and to evaluate its efficacy. Methods: A total of 20 patients with pulmonary small nodules and/or ground-glass opacities, who underwent video-assisted thoracoscopic surgery from August 1, 2017 to March 1 2018, were included in the study. Results: A total of 24 lesions in 20 patients underwent blue-stained glue localization. The success rate of localization was 100%, with a mean dose of 0.04±0.01 mL blue dye and 1 mL glue used for each lesion. The average time for the whole localization procedure was 15.4±6.3 minutes. All lesions were intraoperatively localized by visual inspection in combination with palpation. The complications related to the localization procedure included mild pneumothorax occurring in 9 patients and minor pulmonary hematoma in 4 patients. No pain or distress was reported. Conclusions: Blue-stained glue injection is technically feasible and safe to localize pulmonary small nodules and ground-glass opacities before thoracoscopic resection.